Refugio Pavon memorial - Troncoso Valencia, Lorena (2017)
Refugio Pavón, by the architect Lorena Troncoso Valencia, located in the municipality of Pinto, region of Ñuble - Chile, is located in a small area without trees in the middle of the forest, allowing a  greater sunny and a view of the refuge. It has lush vegetation at the sides and a large wall of natural stone in the background. The use of wood predominates in all its architectural component  creating spaces of a high sensation of warmth.